LOCAL HEMOSTATIC AGENTS IN THE MANAGEMENT OF BLEEDING IN ORAL SURGERY - Kumar MP, Santhosh (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Bleeding intraoperatively and postoperatively in oral surgery poses a great threat to the patient and can lead to serious untoward consequences if uncontrolled. The dentist should be familiar with the range of hemostatic agents available and their application during different types of bleeding episodes. Bleeding complications can occur in healthy as well as systemically compromised patients. Having a broad knowledge of the management approaches will allow the clinician to know when to apply a particular approach. Unfortunately, some of the most useful preventive measures and management techniques are not utilized because of a lack of understanding of the coagulation process and/or the approaches and materials that are available. The purpose of this article is to review the literature regarding the applications of various local hemostatic agents in the management of bleeding in oral surgery, their mechanism of action, and contraindications. Furthermore, the novel hemostatic agents such as HemCon dental dressing and Quikclot are also discussed. Local hemostatic agents are very useful in controlling bleeding during oral surgical procedures in patients with congenital and acquired bleeding disorders and also in patients who are on antithrombotic medications for their systemic conditions. Keywords: Hemostasis, Local hemostatic agents, Oral surgery, Bleeding.